Synthesis, Structural and Optical Properties of PVP Encapsulated CdS Nanoparticles - L. Saravanan; S. Diwakar; R. Mohankumar; A. Pandurangan; R. Jayavel (Nanomaterials and Nanotechnology)
Highly monodispersed CdS nanoparticles using polyvinyl pyrrolidone (PVP) as the capping agent were synthesised by chemical coprecipitation method. The surface‐modified cadmium sulfide nanoparticles were found to be remarkably stable. In the presence of PVP, cubic phase with small grain size of CdS were observed in XRD. The peaks were identified to originate from (111), (220) and (311) planes of CdS, respectively. The crystallite size of the synthesised CdS nanoparticles was about 3 nm calculated from the (111) plane of XRD pattern and it was also confirmed through HRTEM. Morphology and elemental mapping of the synthesised nanoparticles were studied by SEM and EDX analyses. Increase in the band gap with decrease in the particle size was observed from the reflectance mode UV spectrum, which confirms the quantum confinement effect. From the photoluminescence studies, enhanced near‐band‐edge blue light emission and significantly reduced defect‐related green emission were observed. Longitudinal optical (LO) phonon modes, corresponds to pure CdS were observed in Raman spectrum.